Selective oxidation of 1-octanol over gold supported on mesoporous metal-modified HMS: The effect of the support; Catalysis Today; Vol. 227 : Molecular Sieves and Catalysis: Selected papers from CIS-5 Conference - Martinez-Gonzalez S.; Gomez-Aviles А.; Martynyuk O. A. Oksana Anatolievna; Pestryakov A. N. Aleksey Nikolaevich; Bogdanchikova N.; Cortes Corberan V. (2014, 2014)
Title screen